KESADARAN HIDUP SEHAT ANGGOTA SENAM AEROBIK DI SANGGAR SENAM KARTIKA DEWI YOGYAKARTA - M Husni Tamrin (Jurnal Penelitian Humaniora, 2003)
Abstract The research was conducted with the objective of describing the healthy life awareness of aerobic dance members at Kartika Dewi Yogyakarta Gymnasium. The healthy life awareness involved a person habit which was indicated by many factors such as: (1) eating habit, (2) drinking habit, (3) resting habit, (4) personal hygiene, (5) environmental health, and (6) sport and recreation. The population of this research was all the members of the aerobic dance of Yogyakarta Kartika Dewi. The sample technique fulfilling the following requirements: (a) female, (b) age ranging from 20 to 35 years, (c) 3 times a week training, (d)regular training for three months at minimum. The data were analyzed by the descriptive percentage thecnique with the following categories: “Good”, “Average” and “Poor”. The research variable was the healthy life awareness which was measured by using questionnaires consisting of the following factors: (a) eating habit, (b)drinking habit, (c)resting habit, (d) personal hygiene, (e) environmental health, and (f) sport and recreation. The research result showed that the healthy life awareness of aerobic dance members of Kartika Dewi Yogyakarta Gymnasium was as follows: (52.63%) were in “Good” category. Where as the result of the analysis of each factor is as follows: (a) in terms of eating habit, most of the member (67.11%) were in the “Average” category, (b)drinking habit,most of them(72.37%) were in the “Good” category (c)resting habit, most of them (55.26%) were in the “Average” category(d) personal hygiene, most of them (88.16%) were in the ”Good” category( e) environmental health, half of them (50%) were in the “Good” category and (f) sport and recreation, almost half of them (48.68%) were in the “Average” category. Keywords: awareness, healthy life